Wilsonismo e mudanca: analise da abordagem wilsoniana na politica externa das administracoes Bill Clinton e George W. Bush - Camargo, Ana Carolina de Angelo [UNESP] (2012)
The end of the Cold War led to questions about the international order and the position of the United States in particular. At the end of the conflict, the United States had political and military superiority as no other state throughout History. During this period, there was renewed the longstanding desire of America to remodel the order according to its image, ie. the promotion of its values around the world. Thus, the first two presidents elected after the end of the Cold War, Bill Clinton and George W. Bush, retook the wilsonian approach to U.S. foreign policy. At the same time global and regional tensions and the lack of bipolarity influence enable the emergence of problems all around the globe. Not all were directly related to system stability, but still offered challenges for United States foreign policy. This paper seeks, based on the reading of various texts written about the period, to make an analysis on the use of wilsonianism over these governments, emphasizing two distinct periods: the strategy of engagement and expansion in the Clinton administration and the Bush doctrine. The analysis required in the research seeks to show that despite their differences, both used the approach for the same purpose: to justify their actions in foreign policy. The research also presents discussions around the concept of wilsonianism, based on its most fundamental characteristics. Finally, we tried to present the challenges to wilsonian approach in a world still in transformation.